An intersectional perspective on the impacts and responses of entrepreneurs during the COVID-19 pandemic in Germany - David, Alexandra; Terstriep, Judith; Schäfer, Susann; García Schmidt, Armando (International journal of social entrepreneurship and innovation, 2024)
In the wake of the COVID-19 pandemic, research is swiftly progressing to comprehend the impact on solo self-employed individuals and microenterprises. Although there is unanimous agreement within the literature that this unprecedented event has profoundly affected businesses globally, evidence regarding these impacts’ precise direction and extent remains inconclusive. A limited understanding exists concerning the various intersecting factors influencing entrepreneurs’ affectedness and coping strategies. This article employs qualitative interview data to examine how entrepreneurs from knowledge-intensive services and retail and hospitality sectors in Germany experienced, navigated and responded to the multifaceted challenges posed by the COVID-19 pandemic. Results reveal that factors at the intersection of sector affiliation, gender, migrant background and care/parental responsibilities determine entrepreneurs’ affectedness and shape their coping strategies, including using state aid programmes. Highlighting distinct combinations of intersecting factors, we contribute to advancing the ongoing scholarly discourse on crisis dynamics and intersectionality in entrepreneurship and policymaking.